Israelite Temples: Where Was Israelite Cult Not Practiced, and Why - Avraham Faust (Religions, 2019)
Most scholars in the late 20th and early 21st century believed that cultic activity in the kingdoms of Israel and Judah was practiced in various temples that were scattered throughout the kingdoms. Still, a detailed study of the archaeological evidence on Israelite cult reveals that Israelite cultic buildings were extremely rare, both in absolute terms and when compared to other ancient Near Eastern societies, suggesting that cultic activity in temples was the exception rather than the norm and that typical Israelite cult was practiced in the household and in other, non-temple settings. Hence, the evidence suggests that rather than viewing temples, like the one in Arad, as exemplifying typical cultic activity, they should be viewed as exceptions that require a special explanation. The first part of the article develops and updates the suggestion, first raised about ten years ago, that Israelite temples were indeed extremely rare. Given the ancient Near Eastern context, however, such practices seems to be exceptional, and the second part of the article will therefore explain why was such a unique pattern not identified in the past, and will suggest a possible explanation as to how was such an outstanding practice developed and adopted.